Exploring the relationship between professional roles and behavioural intentions in chronic kidney disease management: a cross-sectional study among primary and specialist health professionals in Shanghai, China - Yan Liang; Wenyi Wang; Liutao Wu (BMJ Open)
Objectives General practitioners, nephrologists and renal nurses play key roles in professional integration in chronic kidney disease (CKD) management. Professional roles may influence professionals’ behavioural intentions, namely, the degree to which individuals formulate behavioural plans to attain a behavioural goal. However, little is known about the relationship between professional roles and their behavioural intentions in CKD management. Therefore, in this study, we aimed to explore the relationship between professional roles and their behavioural intentions in CKD management and the mediating role of normative and functional factors.Design Cross-sectional.Setting A cross-sectional survey study was conducted in Shanghai, China.Participants A total of 244 responses were obtained, including 145 from general practitioners, 37 from nephrologists and 62 from renal nurses. We used a self-administered questionnaire to collect data through hospital unit/Community Health Service Centre visits. We performed exploratory factor analysis for behavioural intentions in CKD management. The Karlson-Holm-Breen method was used to decompose the total effect of roles on behavioural intentions in CKD management into direct and indirect (ie, mediational) effects and to calculate the mediated percentage.Results The indirect effect of personal norm (should CKD management be included in daily work or not) accounted for 51.91% of the total effect of nephrologists on one-to-multiple CKD management intentions and 43.79% of the total effect of renal nurses on one-to-multiple CKD management intentions.Conclusion Our results support the mediating pathways of personal norms on the relationship between roles and behavioural intentions, but the mediating role of functional factors was not supported. These findings suggest that enhancing the personal norms of general practitioners may benefit their behavioural intentions in CKD management.